Structural and electrical properties of strontium barium niobate thin films crystallized by conventional furnace and rapid-thermal annealing process - Mendes, R. G. [UNESP]; Araújo, Eudes B. [UNESP]; Eiras, J. A. [UNESP] (My University, 2001)
Strontium barium niobate (SBN) thin films were crystallized by conventional electric furnace annealing and by rapid-thermal annealing (RTA) at different temperatures. The average grain size of films was 70 nm and thickness around 500 nm. Using x-ray diffraction, we identified the presence of polycrystalline SBN phase for films annealed from 500 to 700 °C in both cases. Phases such as SrNb2O6 and BaNb2O6 were predominantly crystallized in films annealed at 500 °C, disappearing at higher temperatures. Dielectric and ferroelectric parameters obtained from films crystallized by conventional furnace and RTA presented essentially the same values.
Keywords: Crystallization; Electric furnaces; Metallorganic chemical vapor deposition; Permittivity; Rapid thermal annealing; Scanning electron microscopy; Strontium compounds; X ray diffraction analysis; Metallic ions; Thin films